The Effectiveness of New Teachers Course in Developing the Teaching Competencies Among the English Teacher in Directorate of Education and Teaching of the Karak Kasabh - Alja'afreh, Hanan Mohammad (Journal of Educational and Psychological Sciences, 2020)
This study aimed to identify the level of The Effectiveness of New Teachers Course in Developing the Teaching Competencies Among the English Teacher In Directorate of Education and Teaching of the Karak Kasabh In Jordan. The study based on the description approach which based on the descriptive method researcher used a questionnaire which consist of (30) items to analyze and process data it was distributed to sample consist of (160) female and male teachers. This sample was chosen randomly. Data was statistically processed by SPSS programme. The result showed that level of Effectiveness was high with level (3.75 /5). The field of classroom management was the highest level with degree (4.03) then field of teacher personality with degree of (3.94) then field of implementation with degree of (3.72) finally the field of planning for lesson with degree of (3.71). - The finding also showed there is no statistically significant differences between the level of English teachers sex (male and female) in addition there were statistically significant differences between teachers of (3 years and less) of experience and these with (3- 6) years of experience in favor of the first group and statistically significant differences between teachers of (3- 6) years of experience and these with (6 and more) years of experience in favor of the second group. - in light of these result there is set of recommendations and suggestion to develop the effectiveness of new teachers program to develop the teaching competences among the English teacher in Jordan and entire Arab countries.